INVENTARISASI KUPU-KUPU DI UNIVERSITAS NEGERI MEDAN - Siregar, Elida Hafni; Simatupang, Halim (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
This reseach aims to known the butterflies species at State University of Medan. Observation and collection ofÂ  butterfliesÂ  were conducted from March â April 2016 at State University of Medan. Butterflies observationÂ  conducted with scan sampling method at 09:00 to 17:00 in sunny days. This study consist ofÂ  found 43 species of butterflies, belonging to 5 families, i.e. Pieridae, Papilionidae, Nymphalidae, Lycaenidae, and Hesperiidae. 15 species of butterflies are found in only one site but 2 species are found in all sites, i.e. Appias olferna and Papilio polytes.